Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1371/journal.pbio.3001843
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of contributing to the citizen science platform iNaturalist as an identifier

Abstract: As the number of observations submitted to the citizen science platform iNaturalist continues to grow, it is increasingly important that these observations can be identified to the finest taxonomic level, maximizing their value for biodiversity research. Here, we explore the benefits of acting as an identifier on iNaturalist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…2019; Martel et al . 2021; Nelson and Moffat 2021; present study), and the contributions of expert iNaturalist identifiers are paramount for detecting species' range extensions (Callaghan et al 2022). However, because of its data format, the iNaturalist database has inherent limitations.…”
Section: Discussionmentioning
confidence: 92%
“…2019; Martel et al . 2021; Nelson and Moffat 2021; present study), and the contributions of expert iNaturalist identifiers are paramount for detecting species' range extensions (Callaghan et al 2022). However, because of its data format, the iNaturalist database has inherent limitations.…”
Section: Discussionmentioning
confidence: 92%
“…Although more work is needed to quantify the identification accuracy across taxa, it is likely that large, colorful, and popular insects such as Lepidoptera, which are likely to be identified correctly by the AI and have many users checking the identifications, have lower rates of misidentification than smaller, less colorful groups. There are many benefits for experts who contribute their knowledge to iNaturalist and other platforms by providing identifications (Callaghan et al 2022), and as more expert-identified records are incorporated the AI identification tool should increase in accuracy. In the meantime, however, we strongly suggest that anyone using iNaturalist data, including those downloading large datasets from GBIF, should validate identifications before data analysis or restrict analyses to charismatic taxa that are more likely to be correctly identified.…”
Section: Resultsmentioning
confidence: 99%
“…From foundational systematic 1,2 , life-history 3 , and conservation studies 4,5 , to continental or global macroecological 6,7 or macroevolutionary analyses 8 , occurrence data are used to understand the natural world and form the basis of research, policy, and management. Spatiotemporal occurrence records (e.g., from specimens, images, or observations) are being delivered to, and produced by, community scientists in quantities that were unthinkable just a decade ago, with ever-increasing identification support by professional experts 9 . However, community-generated records can be biased towards larger and more charismatic taxa 10 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Online repositories, such as the Global Biodiversity Information Facility (GBIF) and Symbiota Collection of Arthropod Network (SCAN), are invaluable data aggregators and tools in supporting the mobilisation of arthropod occurrence data to help both researchers and general audiences understand biodiversity. Concurrently and complementarily, initiatives like iNaturalist and QuestaGame (Australia) enable community and professional scientists to generate occurrence data for research, science communication, and more 9 . Occurrence data are being generated daily, making new analyses possible for previously data-poor taxa.…”
Section: Background and Summarymentioning
confidence: 99%